Electron transfer mediates vibrational relaxation of CO in collisions with Ag(111). Issue 4 (9th November 2018) - Wagner, Roman J. V.; Krüger, Bastian C.; Park, G. Barratt; Wallrabe, Mareike; Wodtke, Alec M.; Schäfer, Tim
Abstract : We report vibrational relaxation probabilities for CO( v = 17) scattered from Ag(111) and compare our results to studies on other molecule–surface systems, which indicates a clear dependence of the relaxation probability on the work function of the surface and the electron binding energy of the molecule. Abstract : We report experimental results on the state-to-state vibrational relaxation of CO( v = 17) in collisions with Ag(111) at incidence translational energies between 0.27 eV and 0.57 eV. These together with previous results provide a comprehensive set of data on two molecules (CO and NO)—one open and one closed shell—and two metals (Ag and Au). In all four cases, the incidence vibrational energy has been varied over several eV. We find a unifying relation between the probability of vibrational relaxation and the energetics of electron transfer from the metal to the molecule. This argues strongly that electronic friction based theories are not capable of explaining these data.